(3TYQ CHj ESMGb GdEdHjQis - (3EHQGgje Hf eSYhO Hf SYjO, CHh ESMGb GdJLjHjGdEdHjQj,J (B460 (3g` s ((3KZQ efQbI s)
(3ChdgG (B:s
(3bGd GdabjI GdRGgO CHhESMGb GHQGgje Hf eSYhO GdEdHjQi JaJ aDGOi GdCjGe aJkG hJfMJ LSec GdSGYGJ fMJG s
(3BNQgG (B:s
(3hdGjcf jMVQfG KGdK aQHeG GdKGdK jShO ajfG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B73s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B216 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs